Bundling of inputs and services for sustainable smallholder agriculture: the concepts, theoretical arguments and bundle designs using conjoint analysis - Tamiru Amanu Abetu; Paul T.M. Ingenbleek; K.E. Giller; Ivo A. van der Lans; Endalkachew Wolde-Meskel (International Journal of Agricultural Sustainability)
Product bundling is receiving increasing attention in sustainable agricultural development as a means to ensure access to and enhance the uptake of, agricultural technologies by smallholders. Yet, the how and why of bundling for smallholders are not well-understood. The current paper, therefore, brings bundling theory from the marketing literature to the smallholder context. We use a conjoint experiment, a proven marketing technique for designing new products, services and bundles, to design agricultural input and service bundles for soybean-producing smallholders in rural Ethiopia. The empirical findings from 252 smallholders suggest that product bundling enhances smallholders’ preferences and hence intentions to adopt technologies but that bundles must be designed carefully following a smallholder-centric approach. Drawing on our findings and the literature, we delineate the different steps that need to be taken to develop bundles for the successful uptake of new technologies by smallholders.